Methods and techniques of business forecasting - Butler, William F.; Kavesh, Robert A.; Platt, Robert B.; Butler, William F. (Englewood Cliffs, N.J. : Prentice-Hall, 1974)
A guide to business forecasting as it is practiced by economists in industry, government and academic life.
First ed. (1966) entered under: Butler, William F., ed. How business economists forecast.
Includes bibliographical references.
oif 06/03/2019
Loans
Keywords: Business forecasting; Economic forecasting